Solution: Solve xy’ (2y – 1) = y (1 – x)

Solve xy’ (2y – 1) = y (1 – x). How to solve differential equations?

Solve xy’ (2y – 1) = y (1 – x)

Problem Statement: EE Board April 1996

Solve xy’ (2y – 1) = y (1 – x)

  • A. ln (xy) = 2 (x – y) + C
  • B. ln (xy) = x – 2y + C
  • C. ln (xy) = 2y – x + C
  • D. ln (xy) = x + 2y + C

Problem Answer:

The solution is ln (xy) = x + 2y + C

Solution:

Latest Problem Solving in Differential Equations

More Questions in: Differential Equations

Online Questions and Answers in Differential Equations


Search! Type it and Hit Enter


Accepting Contribution for Website Operation. Thanks!

Post a Comment

Contact Form

Name

Email *

Message *

Powered by Blogger.
Javascript DisablePlease Enable Javascript To See All Widget